Awakening of consciousness for Humanitarian Approach - Shalini Sharma, Nirmal Sharma, Sandeep Kumar, Shreyanshi Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Life is to live, to enjoy, to learn, to attain divinity. It is given with a mission and motive that can change the course of entire life. The main thing is to recognize and feel that mission by the common human beings who are always surrounded by their own created follies, miseries, confusions and sufferings. That divine goal is higher than earning and spending. Really there should be an awakening of the consciousness that should be freed from all vices and illness. So now the time has come to think higher and try to feel the sense of inner peace and satisfaction. Just try to recognize your capacity and strength; you can get whatever you want. Nothing is impossible but there should the awakening of consciousness for humanitarian approach.